Development of Wound Dressing for Regenerative Medicine - Irina S. Kudryashova; Pavel A. Markov; Elena Yu Kostromina; Petr S. Eremin; Andrey P. Rachin; Ilmira R. Gilmutdinova (Вестник восстановительной медицины, 2021)
The understanding of the pathophysiological mechanisms of the wound process deepened with the development of science. The technological base that was creating has enabled to serve the clinical needs of tissue repair. These factors, combined with the growing need for healing of infected and chronic wounds, have led to the expansion of the market for wound dressings materials supplies. In this connection, there is a need to generalize and update information about new types of dressings. This review provides an up-to-date understanding of the wound process: cellular and signaling mechanisms of repair, characteristics of the optimal microclimate of the wound bed, morphofunctional re-arrangements of tissues during the healing process. Based on these data, the requirements for the modern wound dressings are formulated. Existing wound dressings have been classified as interacting with body tissue. The bio-functional characteristics of the synthetic and natural polymers used in the dressing are described, including their effect on regenerative processes. A classification of the active medicinal ingredients used in the manufacture of dressings is given, the characteristics of their use on the background of the pathological wound process are considered.